Inorganic 3D structures the extended zintl-klemm concept - Vegas, Angel (Structure and bonding, 2011)
Structural relationships between intermetallic clathrates, porous tectosilicates and clathrate hydrates / D. Santamaría-Pérez and F. Liebau -- Crystal structures of inorganic oxoacid salts perceived as cation arrays : A periodic-graph approach / Vladislav A. Blatov -- FeLi[PO₄ ]: dissection of a crystal structure / Angel Vegas -- Rationalization of the substructures derived from the three fluorite-related [Li₆(M(V)Li)N₄] polymorphs: An analysis in terms of the "Bärnighausen trees" and of the "Extended Zintl-Klemm concept" / D.J.M. Bevan, R.L. Martin, and Ángel Vegas -- Concurrent pathways in the phase transitions of alloys and oxides : towards an unified vision of inorganic solids / Angel Vegas.